An extension of the Blinder-Oaxaca decomposition to a continuum of comparison groups - Hugo \~Nopo (Institute for the Study of Labor (IZA), 2007)
This paper proposes an extension of the Blinder-Oaxaca decomposition from two to a continuum of comparison groups. The proposed decomposition is then estimated for the case of racial wage differences in urban Peru, exploiting a novel data set that allows the capturing of mestizaje (racial mixtures).
Keywords: 330; Dekompositionsverfahren; Mikroökonometrie; Lohndifferenzierung; Ethnische Diskriminierung; Städtischer Arbeitsmarkt; Peru